(untitled) (Colombia Medica, 1986)
During one year (1984), neonatal birth results were observed in the Hospital Universitario del Valle in Cali, Colombia. Data from sick newborns were analyzed, looking for specific morbidity and mortality for comparison with those of other hospitals and the same neonatal unit in previous years. It was observed that neonatal mortality was very high when compared with data from an American hospital of similar characteristics, and it has not changed during the last ten years. However, technology and knowledge have improved significantly in handling the sick newborn. The results suggest that to diminish morbidity and mortality, it may be necessary to improve the care given to newborns in peripheral hospitals, and it may raise questions about the advisability of building type 3 neonatal units in areas that don´t give adequate care in levels one and two of regionalization.